THE COMMUNICATION STRATEGIES OF THE MADRASAH PRINCIPAL IN ENHANCING THE COMPETITIVENESS OF AN EDUCATIONAL INSTITUTION: A CASE STUDY OF MI PLUS DARUSSAADAH LIRBOYO - Amik Nadziroh; Ari Susetiyo; Hilma Ildawati (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This research is based on the significance of communication strategies employed by the head of the madrasah in enhancing the competitiveness of educational institutions within an increasingly competitive environment. MI Plus Darussaadah Lirboyo, as a relatively new institution under the auspices of a prominent Islamic boarding school, faces challenges in building a positive image and gaining community trust. This study aims to describe the implementation of the head of the madrasah's communication strategies and the outcomes achieved in strengthening institutional competitiveness. The study applied a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques. The findings reveal that the head of the madrasah implemented personal, social, persuasive, and collaborative communication strategies. These included open communication via social media and regular meetings, persuasive delivery of policies and vision, and collaborative efforts with teachers, parents, and the local community. The impact of these strategies was evident in the improved institutional image, increased student enrollment, and greater stakeholder participation in educational programs. In conclusion, the head of the madrasa's communication strategies play a crucial role in shaping an adaptive, competitive, and sustainable educational environment